SUBMICRON SIZED SINTERED ODS STEELS PREPARED BY HIGH EFFICIENT ATTRITION MILLING AND SPARK PLASMA SINTERING - RACHID BEN ZINE, H.; HORVATH, A.; BALAZSI, K.; BALAZSI, C. (Courrier du Savoir; Vol. 24 (2017): COURRIER DU SAVOIR (Septembre), 2017)
ABSTRACT This paper summarizes recent results for preparation, structural and mechanical investigation of oxide dispersed strengthened steel (ODS). Three commercial steel powders, two austenitic steel and one martensitic powders have been used as starting materials. One of the austenitic powders was used for morphological study during wet milling. The high efficient attrition mills are on the basis of this work assuring grains with nanostructure. The morphological changes during milling steps have been described. It was demonstrated that 4 hours milling in wet atmosphere are enough to realize steel powders with submicron dimensions. An efficient dispersion of nanosized oxides in ODS steels was achieved by employing high efficiency attrition milling. A combined wet and dry milling process of fine ceramic and steel particles has been proposed. Spark Plasma Sintering (SPS) was applied to realize submicron grained steel compacts. Grains with 100 nm mean size have been observed by scanning electron microscopy (SEM) in sintered austenitic ODS. In comparison, the sintered martensitic dry and combined milled ODS microstructure consisted of grain sizes with 100-300 nm in each case. KEYWORDS: ODS Steel, Spark Plasma Sintering (SPS), attrition milling, Nano-oxides, structural and mechanical investigation